Pharmacological Treatment of Obesity: A Review of Current and Future Methods - Lęgas, Angelina; Smalira, Joanna; Przybysz, Bartosz; Kawalec, Jakub; Zawistowska, Julia; Rogowska, Karolina; Pochodowicz, Katarzyna; Rogala, Weronika; Rutkowska-Kawalec, Weronika; Urbańska, Karolina (Quality in Sport, 2024)
Introduction and objective Obesity poses a significant public health challenge due to its association with an elevated risk of various chronic diseases, including cardiovascular conditions, type 2 diabetes, and overall mortality. While lifestyle modifications such as dietary changes and increased physical activity remain cornerstone interventions in obesity management, pharmacological treatments have emerged as an adjunctive approach to address this complex condition. The review aims to compare the effectiveness of current pharmacotherapy and show upcoming methods of treatment of obesity. Review methods The review was conducted by searching scientific publications in PubMed, Google Scholar, Clinicaltrials.gov, Summaries of Product Characteristics, URPL, FDA, and EMA databases. The articles on medications available in Poland for treating obesity and the latest clinical trials of upcoming drugs were analyzed, followed by a concise review of the collected data. Abbreviated description of the state of knowledge Currently, in the Polish market, medications available for obesity treatment include orlistat, the combination of naltrexone and bupropion, liraglutide, tirzepatide, and available as part of the target import - semaglutide. Promising clinical trials are being conducted on further medications for weight reduction, including retatrutide, orforglipron, cagrilintide, and amycretin. Regrettably, new and effective medications due to their high cost and insufficient funding. Summary New pharmacotherapy options for obesity, particularly anti-diabetic medications, are rapidly advancing. Glucagon-like peptide-1 (GLP-1) analogs have shown promising results in weight reduction, surpassing previous medications such as orlistat or naltrexone. Recent drugs offer weight loss ranging up to 25%. More studies are underway on novel and increasingly effective medications.